2019
DOI: 10.1111/pcn.12820
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and post‐traumatic stress disorder

Abstract: While post‐traumatic stress disorder (PTSD) is currently diagnosed based solely on classic psychological and behavioral symptoms, a growing body of evidence has highlighted a link between this disorder and alterations in the immune and inflammatory systems. Epidemiological studies have demonstrated that PTSD is associated with significantly increased rates of physical comorbidities in which immune dysregulation is involved, such as metabolic syndrome, atherosclerotic cardiovascular disease, and autoimmune dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
197
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(220 citation statements)
references
References 162 publications
(203 reference statements)
6
197
0
17
Order By: Relevance
“…In the current review, IL-6 demonstrated to be the most documented proinflammatory cytokine in human models of PTSD, and the majority of studies demonstrated increased IL-6 levels in the serum sample of individuals diagnosed with PTSD as compared with their respective control group. This may also be in alignment with previous research which noted IL-6 as the most considerable marker for inflammation [21]. Specifically, studies have shown that IL-6 is crucial in the relationship between immune system and CNS in inflammatory states [44].…”
Section: Roles Of Proinflammatory Cytokines In Ptsd: Il-1β Il-6 Tnfsupporting
confidence: 90%
See 3 more Smart Citations
“…In the current review, IL-6 demonstrated to be the most documented proinflammatory cytokine in human models of PTSD, and the majority of studies demonstrated increased IL-6 levels in the serum sample of individuals diagnosed with PTSD as compared with their respective control group. This may also be in alignment with previous research which noted IL-6 as the most considerable marker for inflammation [21]. Specifically, studies have shown that IL-6 is crucial in the relationship between immune system and CNS in inflammatory states [44].…”
Section: Roles Of Proinflammatory Cytokines In Ptsd: Il-1β Il-6 Tnfsupporting
confidence: 90%
“…Here, the premise is that individuals who are at risk for PTSD have a distinct proinflammatory state prior to any exposure to trauma as compared with resilient individuals. Another perspective is the distinct responsiveness towards trauma that may vary according to genetic factors [21], such as the ALOX12 locus as described in Table 4 [74]. Since the activation of many genes including ALOX12, ALOX15, and RORA have shown to alter according to oxidative stress in a PTSD model [108], a targeted approach that observes for the relationship between inflammation and trauma exposure according to genetic variants may identify the risk or resilience factors of PTSD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Posttraumatic stress disorder (PTSD) is a debilitating psychiatric condition characterized by intrusion, avoidance, hyperarousal, and other symptoms, which occurs in response to an array of traumatic events including physical, sexual, or mental abuse; wartime experiences; or being the victim of a violent crime [1]. The resulting stress can cause a pro-inflammatory response in the brain characterized primarily by the complex release of inflammatory mediators such as cytokines, prostanoids, free radicals, and transcription factors, as well as subsequent brain inflammatory responses, which further contribute to cell damage [2,3]. Conventional treatment for PTSD includes pharmacotherapy, psychotherapy, and psychophysiological therapy, although it is often resistant to these treatments [4].…”
Section: Introductionmentioning
confidence: 99%